2016
DOI: 10.1080/10810730.2016.1177141
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent and Young Adult Perceptions of Hookah and Little Cigars/Cigarillos: Implications for Risk Messages

Abstract: Use of hookah and little cigars/cigarillos (LCCs) is high among adolescents and young adults. Although these products have health effects similar to cigarettes, adolescents and young adults believe them to be safer. This study examined adolescent and young adult perceptions of hookah and LCCs to develop risk messages aimed at discouraging use among users and at-risk nonusers. Ten focus groups with 77 adolescents and young adults were conducted to explore their perceptions about the perceived risks and benefits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 32 publications
5
81
1
Order By: Relevance
“…This finding is unexpected given that other studies reported that youth perceived cigars to have lower health risks than cigarettes. 15,25,26 Although youth may hold beliefs that cigarillos are less harmful than cigarettes, our study findings show that these are not commonly endorsed reasons for initiation. For adolescents, avoiding long-term health risks may not be a compelling reason to initiate and/or discontinue tobacco use because they may believe that they can quit easily, 44 and that negative health effects from cigarillos are less likely to happen to them because they do not use it regularly.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This finding is unexpected given that other studies reported that youth perceived cigars to have lower health risks than cigarettes. 15,25,26 Although youth may hold beliefs that cigarillos are less harmful than cigarettes, our study findings show that these are not commonly endorsed reasons for initiation. For adolescents, avoiding long-term health risks may not be a compelling reason to initiate and/or discontinue tobacco use because they may believe that they can quit easily, 44 and that negative health effects from cigarillos are less likely to happen to them because they do not use it regularly.…”
Section: Discussioncontrasting
confidence: 57%
“…24 Existing evidence suggests that youth perceive cigar products as less harmful than cigarettes. 15,25,26 If adolescents are initiating cigarillos because they perceive cigarillos to have lower harm than cigarettes, then education and prevention campaigns can focus on informing youth about the health risks of cigarillos relative to cigarettes.…”
Section: Introductionmentioning
confidence: 99%
“…Responses to open-ended items were coded and analyzed using an iterative, constant comparison method where responses are reviewed, initial codes are developed, responses are re-reviewed, codes are revised, and applied to the data 47,48 . Similar methods were used in recent studies of youth and young adult perceptions of WTS and other emerging tobacco products 22,[49][50][51][52] . Two trained coders reviewed open-ended responses independently to inductively identify common themes in the data, developed a codebook comparing themes identified, and coded the data.…”
Section: Analytic Strategymentioning
confidence: 99%
“…Despite evidence to the contrary, many young adults maintain the belief that WTS is less addictive than cigarettes [20][21][22] . However, much of the evidence on young adults' WTS beliefs and perceptions comes from population surveillance surveys [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation